La migration des religieux français vers le Canada (1880-1914) : territoires de l’attente et spiritualité de l’exil - Simon Balloud (Nuevo mundo - Mundos Nuevos, 2016)
Between 1880 and 1914, Catholic community members leave France under the pressure of the succeeding anticlerical Republican governments’ politics. Forced into exile, two thousands of them migrated to Canada to pursue their work. This particular phenomenon, neglected by religious and migration history, drives a transatlantic missionary migration system since the beginning of the XIXe century. This article puts forward how the multiple « territoires de l’attente » found throughout the journeys of French religious, favor the development of a « spiritualité de l’exil » in them. It will also explain the important role of analyzing letters and travel journals when studying religious migratory experience, through the case of Augustin Leroy, a religious from Sainte-Croix exiled to Canada in 1903.